Low-frequency wake dynamics for a square-back vehicle with side trailing edge tapers. Issue 184 (January 2019) - Pavia, Giancarlo; Passmore, Martin; Varney, Max
Abstract: In this paper, the effects of side trailing edge tapering on the wake of a simplified square-back vehicle are investigated. The tapered surfaces are reported to trigger a switch from a laterally asymmetric bi-stable wake to a vertically asymmetric stable wake. The wake structure reported in the literature for lateral symmetry breaking states is seen to rotate by 90 ∘ as the angle of the tapered surfaces ϕ s is increased. A 6 % drag reduction over the simple square-back case is reported for 6 ∘ < ϕ s < 12 ∘ . This gain is found to be the result of the stretching of the circular vortex responsible for the suction zone visible in any symmetry breaking state. A downwash dominated wake is observed in these conditions. The sensitivity of such a wake to small variations of the model pitch angle (for ϕ s = 12 ∘ ) is also assessed. As the pitch angle α is reduced from 0 ∘ to − 2 ∘, the time averaged wake is reported to switch from a downwash dominated topology to an upwash dominated topology. A strengthening of the long-time instability is observed when the symmetry in the vertical direction is recovered and is accompanied with a 4.9 % reduction in base drag over the same model tested at α = 0 ∘ . Graphical abstract: Highlights: Side edge tapers can suppress the long-time instability while also reducing drag. The long-time instability stems from the equilibrium between all shear layers. Small perturbations of pitch angle can turn stable wakes into multi-stable wakes. For a square-back bluff body, a lower drag wake is not always a more stable wake.